Сравнительный анализ современных тенденций развития украинской и русской терминографической критики - Петрова, Татьяна (Studia Rossica Posnaniensia, 2020)
Compiling special dictionaries in Ukraine and Russia has its own history, national specifics, significant achievements and groundworks. Terminological dictionaries play an important role – they preserve and transmit the scientific terminology fund from generation to generation, which necessitates a critical examination of each specific publication. Terminographic criticism is an integral, interdisciplinary direction which is formed simultaneously on the basis of scientific criticism and scientific communication combining their features. As a result of the study, it was established that modern Ukrainian and Russian critics in their reviews adhere to the same principles to examine terminological dictionaries: the intention to comprehensively analyse, first of all, definition and translation publications as well as reference dictionaries, regarding the representation of their mega-, macro- and microstructure parameters; determining the national and linguacultural values of branch dictionaries. The potential importance of the practical application of the results lies in improving the theoretical and methodological principles and foundations of compiling terminological dictionaries, as well as their use in the development of new models of special publications, in particular dictionaries of a new type, which will comprehensively present the terminology of a certain field of science.